(untitled) (INNOVATIVE ECONOMY, 2021)
Voloshchuk Yu.O. STRATEGIC DIRECTIONS OF INNOVATIVE DEVELOPMENT OF AGRO-INDUSTRIAL ENTERPRISES IN THE CONTEXT OF NEO-INDUSTRIALIZATION Purpose. The aim of the article is substantiation of expediency of use of theoretical and methodical tools of definition of a real and effective direction of innovative development and the further formation of practical bases of effective functioning of agro-industrial enterprises. Methodology of research. General scientific and special methods were used in the process of research, in particular: dialectical, monographic and system analysis – to substantiate the essence of innovative development, strategic development; abstract and logical, tabular, graphic – in the formation of strategic directions of innovative development of enterprises, presentation of ratings and indices of readiness for innovative development, etc. Findings. It is determined that the innovative development of agro-industrial enterprises in the conditions of neo-industrialization of modernization is realized in three stages: ability; opportunities; readiness to implement a strategic direction. A differentiated analysis was conducted on the basis of generalization, substantiation and specification of methodological and practical approaches to the ability, ability and readiness for innovation and investment development to determine the real and effective direction of innovation development, and also the set of factors influencing efficiency of practical realization of modernization of the agro-industrial enterprises in the context of neo-industrialization is defined by an expert way by a method of Delphi. It is proved that the strategic directions of innovative development of agro-industrial enterprises in the context of neo-industrial modernization are intellectualization of neo-industrial innovations, integration of enterprises with scientific organizations, creation of innovation clusters as associations of enterprises, Institution of higher education, scientific and financial institutions and other organizations and the introduction of certain innovative elements. The generalized estimation of readiness for innovative development of the enterprises on their sizes on signs by definition according to the normalized correlation coefficients and the certain range of probable changes is given. The definition of “innovative activity of the enterprise” has been supplemented. The achieved level of Ukraine’s ability to master advanced technologies, which is assessed by the Index of readiness for advanced / breakthrough technologies according to the world rating is studied. Originality. The strategic directions of innovative development of agro-industrial enterprises in the context of development of innovation system in the conditions of neo-industrialization are generalized. Practical value. The obtained results of the study can be used to determine the potential for innovation, taking into account a set of factors that promote or hinder innovation, as well as components of the ability, capabilities and readiness of small, medium and large enterprises of agro-industrial complex for such development based on building a matrix of choice of strategic alternatives within the framework of innovative business. Key words: innovative development, enterprise, innovations, strategic development, opportunities.